Evaluation of Traditional Medicine Label Compliance Based on CPOTB: Post-Market Surveillance in the Working Area of BPOM Kediri - Lindawati Setyaningrum; Fenti Indah Nirwana; Dian Reny Agustina (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Introduction. Post-market surveillance of traditional medicines is an essential regulatory activity to ensure product quality, safety, and the accuracy of information provided to consumers. One critical component of such surveillance is evaluating the compliance of product labels with applicable regulatory requirements. Aim. This study aimed to assess the conformity of traditional medicine labeling with the implementation of Good Manufacturing Practices for Traditional Medicines (CPOTB) within the working area of BPOM Kediri as part of a risk-based post-market regulatory strategy. Method. This applied observational study employed a descriptive cross-sectional design. Data were obtained from post-market surveillance activities through sampling of 30 traditional medicine products collected from pharmacies, herbal shops, modern retailers, and traditional markets within the BPOM Kediri jurisdiction during 2023–2025. Label conformity was evaluated using a CPOTB-based checklist in accordance with BPOM Regulation No. 25 of 2021. Data were analyzed descriptively to identify compliance profiles and dominant non-compliance categories. Result. A total of 30 findings of non-compliance were identified from 30 product samples, demonstrating an increasing trend over the three-year period. The most frequent non-compliance indicators were excessive or misleading claims (30.0%), absence of batch or lot numbers (26.7%), and absence or misuse of marketing authorization numbers (23.3%). These findings indicate potential risks related to consumer protection, product traceability, and regulatory assurance. Conclusion. Systematic evaluation of traditional medicine labeling through post-market surveillance serves as a strategic regulatory instrument to strengthen oversight, enhance consumer protection, and support effective implementation of CPOTB in Indonesia.